Cognitive support technologies for people with TBI: current usage and challenges experienced. - Chu, Yi; Brown, Pat; Harniss, Mark; Kautz, Henry; Johnson, Kurt (Disability & Rehabilitation: Assistive Technology, 2014)
Purpose: We investigated the current use of off-the-shelf cognitive support technologies (CSTs) by individuals with traumatic brain injury (TBI), the challenges they and their caregivers face when using these technologies, the functional areas where support is needed, and their current experience in learning new technologies. Method: We conducted two focus groups with participants with TBI and their caregivers. Focus group interactions were captured using recordings and a court reporter. Transcripts were analyzed qualitatively. Results: We identified three core themes - consumer and caregiver self-reported needs for support, how support is used on a daily basis and consumer and caregiver attitudes towards the use of support by types of support. We also inferred implications for design of CSTs. Conclusions: Individuals with TBI use consumer available technologies to support cognition. The design of most of these devices is not targeted to meet the needs of people with TBI, and they can be challenging to use independently, but individuals and their caregivers still benefit from their use by embedding technology as one type of support within a broader support network that includes personal assistance.